STUDYING SCIENCE LEARNING AND TEACHING SYSTEMS IN INDONESIA AND RUSSIA - Raihan, Raihan Muhammad; Eliza, Sindi Nova; Efreyanti, Niken (MEDIA DIDAKTIKA, 2025)
Science education plays a crucial role in advancing technology and innovation, especially in the era of the Industrial Revolution 4.0 which demands mastery of STEM (Science, Technology, Engineering, and Mathematics) competencies. However, the implementation of science education varies greatly between countries. This study aims to compare the teaching and learning systems of science, particularly physics, in Indonesia and Russia through a qualitative comparative approach. Data were collected from literature reviews including journal articles, books, educational reports, and policy documents. The analysis reveals that Russia employs a more structured science curriculum supported by intensive teacher training and a strong research-based teaching culture from an early age. In contrast, Indonesia still faces challenges such as limited laboratory facilities, uneven teacher training, and a lack of integration between theory and practice. These disparities result in lower science literacy performance among Indonesian students in international assessments like PISA, compared to their Russian counterparts. The study concludes by offering strategic recommendations for improving science education in Indonesia, including enhancing teacher training programs, strengthening policy support, and adopting experimental learning approaches inspired by the Russian model. This research contributes theoretically to the literature on international education comparisons and provides practical insights for policymakers and educators aiming to develop more effective science teaching strategies.